Kebutuhan remaja untuk mengirim foto atau video di Instagram - Setiasih Setiasih; Florencia Inne Puspitasari (Jurnal Psikologi Ulayat, 2015)
Instagram is one of the most popular social media, that focus on photo sharing. Survey of MarkPlus Insightshowed tha t5.9% users are adolescence, aged 15- 22 years old. By posting photo or video at instagram adolescence connected with people around the world. It means that they got the need of affiliation. This study conducted to know the needs of adolescence for posting photo or video at instagram. Participants of this study are 103 adolescence, aged 15-18 years old, has an instagram account, and at least they posted 1-2 photos or videos for a month. This study used a snowball sampling, and data was analyzed with ANAVA.Results of this study showed there are four needs that had made adolescence posting a photo or video at instagram, theywere the need of self explanation, the need for receiving and giving attention to the others, the need for good appearance, and the need for getting social support.Suggestion for adolescence: they have to be aware about the tendency for exploitation photo or video on the instagram.